A Web Based Help Desk System Using Open Source Software - Fadhilah, Aman (2005)
This project aims to develop a working prototype of a web based help desk application using Object Oriented approach and Open Source software. Three main phases were involved in this project, which are defining requirements, analyze requirements and validate requirements. The requirements are defined in a way that they are suitable to be used by small to medium sized companies. The requirements are analyzed by constructing use case diagram, use case specifications, class diagram, activity diagrams and the list of requirements. A working prototype is developed using open source software to validate the requirements. The prototype can be readily used by small to medium sized companies, and can be a base for them to develop their own help desk system that includes other requirements and enhancements which are deemed fit for their needs.